AI-Based Interactive Powerpoint on Photosynthesis and Chemical Reactions - Saidatur Rahmi; Richa Purmaya Sari; Adi Hartono (Universitas Samudra, 2026)
Photosynthesis and chemical reactions are essential concepts in biology and chemistry learning; however, students often experience difficulties in understanding these topics due to their abstract characteristics and complex processes. The integration of artificial intelligence (AI) in interactive learning media is considered capable of improving students’ conceptual understanding and engagement in science learning. This study aimed to develop and evaluate an AI-Based Interactive PowerPoint on photosynthesis and chemical reactions for biology and chemistry education. This research employed a Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The developed media integrated AI-assisted explanations, animations, interactive quizzes, and visual simulations. The research participants were students from biology and chemistry education programs. Data were collected through expert validation sheets, practicality questionnaires, and pretest-posttest instruments. The obtained data were analyzed descriptively and quantitatively using percentage analysis and N-gain scores. The findings showed that the AI-Based Interactive PowerPoint achieved a very valid category based on expert assessment and was considered highly practical by students and lecturers. Furthermore, the media effectively improved students’ understanding of photosynthesis and chemical reaction concepts, as indicated by the increase in posttest scores and positive student responses toward the learning process. The integration of AI features also encouraged more interactive, visual, and student-centered learning experiences. In conclusion, the AI-Based Interactive PowerPoint is feasible and effective as an innovative learning medium for integrated biology and chemistry education. The developed media can support meaningful science learning and enhance students’ engagement and conceptual understanding in the digital learning era.